OPTIMISATION OF THE STAFF MOTIVATION SYSTEM IN THE HOTEL BUSINESS - Horozhankina, N. A.; Saihak, Ye. L.; Grytsenko, A. V.; Topol, D. S. (Systems and Technologies, 2025)
The personnel motivation system is considered on the example of LLC "Hotel World (the hotel "Dnipropetrovsk")". Based on the questionnaire method, a check was made of the compliance of the existing personnel motivation system with the requirements of the company’s employees. The compliance of the existing personnel motivation system with the requirements of the company’s employees was checked by means of a questionnaire using a specially developed questionnaire. All hotel employees (100%) participated in the questionnaire. Factors of employee dissatisfaction with their work were identified, and the need to improve the personnel policy for employees was assessed. 38% of respondents are completely satisfied with their work in the institution, 43% are more satisfied than dissatisfied, 14% are more dissatisfied and 5% are completely dissatisfied. It was found that 60% of employees are satisfied with the organisation of their workplace, 40% are completely or partially dissatisfied. An assessment of the motivation system was conducted to assess the motivation system of the staff of the hotel "Dnipropetrovsk". It was found that many motivational elements of the hotel "Dnipropetrovsk" require improvement. The main problems associated with the motivation system are: lack of assessment of well-organised professional development and training activities for staff; lack of an adaptation process for employees; lack of career planning for employees; lack of awareness of employees; low level of financial incentives for employees. As a result of the audit of the personnel management system of the hotel "Dnipropetrovsk", it was found that the staff motivation system at the hotel needs improvement, which affects labour productivity. The following measures are recommended to improve the staff motivation system at the hotel "Dnipropetrovsk": 1. Implement an effective staff motivation system that increases labour productivity. When using schemes and bonuses in the salary structure, there should be a clear connection between the contribution of a particular employee and the amount of compensation. 2. Improve the system of material and non-material incentives for employees, including the introduction of additional salary payments at the end of the year, the issuance of certificates of the best employees, etc. A SWOT analysis of the staff motivation system of the hotel "Dnipropetrovsk" was conducted, based on which the shortcomings of the staff motivation system were identified: the staff motivation system is represented only by wages in the form of direct compensation and is practically limited; failure to use the entire motivational potential of employees to improve existing processes and results of the enterprise. The main opportunity of the hotel "Dnipropetrovsk" is to gain time during the recovery period after the economic crisis, reconstruction after Ukraine’s victory in the war with russia and use it to develop a motivation system that meets modern market conditions.